An Introduction to Recording, Editing, and Streaming Picture‐in‐Picture Ultrasound Videos. Issue 8 (18th August 2016) - Rajasekaran, Sathish; Hall, Mederic M.; Finnoff, Jonathan T.
Abstract: This paper describes the process by which high‐definition resolution (up to 1920 × 1080 pixels) ultrasound video can be captured in conjunction with high‐definition video of the transducer position (picture‐in‐picture). In addition, we describe how to edit the recorded video feeds to combine both feeds, and to crop, resize, split, stitch, cut, annotate videos, and also change the frame rate, insert pictures, edit the audio feed, and use chroma keying. We also describe how to stream a picture‐in‐picture ultrasound feed during a videoconference.